2019
DOI: 10.18549/pharmpract.2019.2.1373
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of drug therapy problems identified with a telephonic appointment-based model of medication synchronization

Abstract: Objectives: To describe the drug therapy problems (DTPs) identified for patients enrolled in an Appointment Based Model (ABM) for medication synchronization, describe the pharmacist-delivered clinical interventions, and assess what patient characteristics are associated with the number of DTPs identified. Methods: A cross-sectional chart review of 1 month of pharmacist notes for telephone ABM encounters at one independent community pharmacy in the Midwest U.S. was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…where from 1 month to 10 years, 12,52 with an average intervention length of 15.4 (±15.6) months. The number of MTPs identified ranged from 19 to 38 631, and the number of included patients ranged from 11 to 9068.…”
Section: The Length Of the Interventions Described In The Studies Lasted Any-mentioning
confidence: 99%
“…where from 1 month to 10 years, 12,52 with an average intervention length of 15.4 (±15.6) months. The number of MTPs identified ranged from 19 to 38 631, and the number of included patients ranged from 11 to 9068.…”
Section: The Length Of the Interventions Described In The Studies Lasted Any-mentioning
confidence: 99%
“…Study designs varied, with 1 (4%) randomized controlled trial, 24 3 (11%) quasiexperimental studies, 7,25,26 10 (41%) retrospective cohort studies, [27][28][29][30][31][32][33][34][35][36] 4 (15%) pre-post studies, 37-40 1 (4%) prospective cohort study, 41 1 (4%) cost-benefit analysis, 42 6 (19%) cross-sectional surveys, [43][44][45][46][47][48] and 1 (4%) chart review. 10 Med-sync was provided at different pharmacy settings, such as independent, chain, outpatient, and mail-order pharmacies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 studies, 26 were observational and had moderate to serious bias due to confounding and bias in selection of participants for the study (Table B1). 7,10,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47] All the non-randomized studies had a moderate bias in measurement of outcomes, while two studies had serious bias in measurement of outcomes. 42,48 Confounding was commonly seen as most of the med-sync programs were in conjunction with other programs, such as Medication Therapy Management (MTM), home delivery services, medication reconciliation, adherence packaging, or educational interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the 2-month timeframe of this pilot coupled with the program occurring during the first year of the COVID-19 pandemic did not enable us to realize the full financial potential for new vaccination opportunities. Fitzpatrick and colleagues conducted a retrospective study describing drug therapy problems identified in patients enrolled in an appointment-based model [ 22 ]. They found that vaccine recommendations were the second most commonly documented intervention.…”
Section: Discussionmentioning
confidence: 99%